Adoption of Entrepreneurial Behavior in Maintaining Business Continuity (Study on Liana Swalayan through Dart Method) - M. Kennix Blue; R Gegha Para Kamanda (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
MSMEs experienced a decline in productivity and profits due to government regulations related to the COVID-19 outbreak. The existence of operational restrictions and regional quarantines impacts the decline in people’s purchasing power. The actors have not been able to adopt entrepreneurial behavior in maintaining business continuity during the pandemic. The research objective is to determine the effect of entrepreneurial behavior on business continuity. The research method used is a qualitative descriptive approach with purposive sampling as a resource withdrawal technique. Sources of data were obtained through interviews, observation, and documentation. Data analysis techniques through data collection, data reduction, data presentation, and concluding. Determination of the sample using a snowball sampling technique. The basis for determining the questionnaire using the DART method (Dialogue, Access, Risk-Assessment, and Transparency) is associated with the research object. The results of the study, namely entrepreneurial behavior, have a positive effect on business continuity. It is evidenced by Liana Swalayan’s ability to maintain its business during a pandemic by implementing general strategies as core competencies.